THE ANALYSIS OF RURAL-URBAN LINKAGE IN ACEH SINGKIL DISTRICT - Hilda Syahrani; Agus Purwoko; Rujiman Rujiman (JURNAL GEOGRAFI, 2021)
Aceh Singkil District is an agricultural area whose the economic activities are dominatated by the farm. There are indications that the economic linkages between rural and urban area have not fully supported the oil-palm farm activities. It resulted the regional development process did not run optimally, so that, it has not made a significant contribution to the public’s welfare. This study aims to identify the economical linkage between the rural and urban areas in Aceh Singkil District. This study used a qualitative approach with the data collection methods through interviews that were descriptively analyzed. The economical linkage can be seen from the capital flow, the shopping flow, the raw material flow, the intermediate goods flow, and the income flow. Based on the linkages between urban and rural areas, it is related to the condition of regional development in Aceh Singkil District. The results showed that the economical linkage were well-established is the shopping flow, while the capital flow was less bind up with villages in the urban area. There were also the raw material flow, the intermediate goods flow, and the income flow that were not absolutely interrelated. The intermediate good flow was binding up with the outside region, so that the acquisition of added value entered other areas. The implication from the conditional linkage of rural and urban areas in the regional development context is that the rural and urban areas are less functionally intertwined. It resulted the high poverty rates in Aceh Singkil District.Keywords: Regional Development, Economical Linkage, Rural-Urban Areas, Oil-PalmKabupaten Aceh Singkil merupakan daerah pertanian yang kegiatan ekonominya didominasi perkebunan. Terdapat indikasi bahwa keterkaitan ekonomi antara perdesaan dan perkotaan belum sepenuhnya mendukung aktivitas perkebunan kelapa sawit. Hal ini mengakibatkan proses pembangunan daerah tidak berjalan dengan optimal sehingga belum memberikan kontribusi yang signifikan terhadap kesejahteraan masyarakat. Penelitian ini bertujuan untuk mengidentifikasi keterkaitan ekonomi antara perdesaan dan perkotaan di Kabupaten Aceh Singkil. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data melalui wawancara yang dianalisis secara deskriptif. Keterkaitan ekonomi ditinjau dari aliran modal, aliran belanja, aliran bahan baku, aliran barang setengah jadi, dan aliran pendapatan. Berdasarkan keterkaitan antara perdesaan dan perkotaan tersebut lalu kaitkan dengan kondisi pengembangan wilayah di Kabupaten Aceh Singkil. Hasil penelitian menunjukkan bahwa keterkaitan ekonomi yang terjalin dengan baik yakni aliran belanja, sedangkan aliran modal kurang terjalin dengan desa-desa yang berada di perkotaan. Adapun aliran bahan baku, aliran barang setengah jadi dan aliran pendapatan sama sekali tidak terjalin. Bahkan, aliran barang setengah jadi terjalin menuju keluar wilayah sehingga perolehan nilai tambah masuk wilayah lain. Implikasi dari kondisi keterkaitan perdesaan dan perkotaan dalam konteks pengembangan wilayah yakni wilayah perdesaan dengan perkotaan kurang terjalin secara fungsional. Hal ini mengakibatkan tingginya angka kemiskinan di Kabupaten Aceh Singkil.           Kata Kunci: Pengembangan Wilayah, Keterkaitan ekonomi, Perdesaan Perkotaan, Kelapa Sawit